Obsessive Compulsive Tic Disorder: appropriate diagnosis and treatment as key elements to improve health and rationalize use of resources (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Obsessive Compulsive Tic Disorder (OCTD) has been described recently as an early onset and highly disabling endophenotype of Tic Disorder and Obsessive Compulsive Disorder. OCTD has a relevant but largely unknown clinical, social and economic burden for patients and their families. Our paper aimed to explore relevant aspects of the burden of OCTD. Methods: we conducted a literature review and a pilot study using retrospective demographic, clinical and economic data of patients with OCTD accessing the Galeazzi Hospital in Milan. Results: the literature review shows the absence of information on OCTD. From the pilot study we analysed data of 30 patients (80.0% male, 36.7% aged from 7 to 13 years, 63.3% aged from 15 to 48 years), 83.0% declared that obsessions and/or compulsions were the most important factors determining their social impairment. Adult patients refractory to drug treatment underwent Deep Brain Stimulation plus drugs. The mean clinical scores at the time of diagnosis indicated a severe condition for both tics and obsessive compulsive components. The mean time elapsed from symptoms onset to diagnosis of OCTD was 5.6 years, reaching up to 11 years in one case. Before reaching the correct diagnosis, different specialists visited the patients several times, 93.3% underwent diagnostic examinations and 86.7% took 2 or 3 different drugs. Ten patients were hospitalised and 8 had received psychotherapy. Discussion: Albeit preliminary, these results show that attention is mandatory for establishing correct diagnosis and treatment guidelines to improve health and rationally spend resources for OCTD.